2017
DOI: 10.1002/bbb.1756
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability assessment of glucose production technologies from highly recalcitrant softwood including scavengers

Abstract: The utilization of abandoned lignocellulosic residues for chemical production has a strong potential to partially substitute chemicals, which are traditionally produced from non-renewable resources. Softwood especially, with its high availability, presents a sustainable resource for the conversion to higher value-added products such as biofuels and bioplastics. In this study, we investigate mature and innovative technologies for the conversion of softwood to the platform chemical sugar from an economic and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 33 publications
(42 reference statements)
1
15
0
1
Order By: Relevance
“…A recent theoretical assessment of glucose production technologies from softwood has shown that the scavenger process at its current stage already has the potential to considerably cut biorefinery operating costs compared to, e.g., a state-of-the art SO 2 pretreatment [ 49 ]. In the overall process cost of a scavenger process, the 2-naphthol additive ranked third after biomass and enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…A recent theoretical assessment of glucose production technologies from softwood has shown that the scavenger process at its current stage already has the potential to considerably cut biorefinery operating costs compared to, e.g., a state-of-the art SO 2 pretreatment [ 49 ]. In the overall process cost of a scavenger process, the 2-naphthol additive ranked third after biomass and enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Las coníferas han sido reconocidas como materias primas altamente recalcitrantes a la hidrólisis enzimática (Morales et al, 2017). El carácter recalcitrante de los materiales lignocelulósicos es debido a la resistencia de la pared celular, que evolucionó como barrera a agentes externos y de degradación.…”
Section: Pretratamientos/ Fraccionamientosunclassified
“…Softwoods have been recognized as a highly recalcitrant raw material to EH (Morales et al, 2017). Several studies and reviews in the last years include generically softwoods, mixed softwoods or refer mostly to spruce and fir as a source for bioethanol production (Pan et .…”
Section: Pine and Eucalyptus Pretreatments For Bioethanol Productionmentioning
confidence: 99%